Hubungan Pengetahuan Interaksi Obat dengan Perilaku Konsumsi Obat Harian Mahasiswa Farmasi: The Relationship Between Drug Interaction Knowledge and Daily Medication Consumption Behavior Among Pharmacy Students at Universitas Muhammadiyah Purwokerto - Nafisa Airlangga; Riski Rahmawati Sandi (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2026)
Understanding drug interactions is essential for promoting safe medication use, particularly among pharmacy students who possess fundamental pharmaceutical knowledge. This study aimed to analyze the association between knowledge of drug interactions and daily medication use behavior among pharmacy students at Muhammadiyah University of Purwokerto. A descriptive quantitative study with a cross-sectional design was conducted involving 23 students who met the inclusion criteria. Data were collected using a questionnaire covering medication history, knowledge of drug interactions, and daily medication use behavior. Descriptive statistics and the Chi-square test were applied with a significance level of α = 0.05. The results showed that 95.7% of respondents had used medication within the previous month, 78.3% demonstrated good knowledge of drug interactions, and 34.8% exhibited good medication use behavior. A significant association was found between knowledge of drug interactions and daily medication use behavior (χ² = 8.42; p = 0.038). However, good knowledge did not consistently translate into safe medication practices, highlighting the need for strengthened educational interventions on evaluating potential drug interactions before concomitant medication use.